Salvage total hip arthroplasty (THA) for failed internal fixations of proximal hip fractures - S. Kawade, Manish; S. Madan, Harnam (International Journal of Research in Medical Sciences, 2017)
Background: Failed proximal femoral fractures like operated transcervical neck fractures, intertrochanteric fractures and subtrochanteric fractures poses a great challenge to surgeon with limited options. Revision of failed internal fixation with hip arthroplasty, also known as Salvage THA (Total Hip Arthroplasty) is a promising surgical option in elderly patients providing early mobility and preventing age related complications. Methods: 45 patients with failed proximal hip fractures were treated over a period of 2 year with THA with modular cemented prosthesis by southern approach. Results: Fourty five patients were followed up for atleast 16 months with no radiological evidence of loosening and heterotrophic ossification and analyzed for pain, difficulty in walking, muscle power, range of motion of joint and functional status. The overall results were expressed in terms of Salvati-Wilson hip grading system. Conclusions: Revision of failed internal fixation with hip arthroplasty, also known as Salvage THA (Total Hip Arthroplasty) is a promising surgical option in elderly patients providing early mobility and preventing age related complications.